2008
DOI: 10.1029/2008gl035769
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term climatology of North Atlantic polar lows

Abstract: [1] A dynamical downscaling of the 6-hourly 1948 -2006 NCEP/NCAR re-analyses for the subarctic region of the North Atlantic has been used to derive a climatology of polar lows by means of a tracking algorithm based on the simulated bandpass filtered MSLP-fields. This climatology is consistent with the limited observational evidence in terms of frequency and spatial distribution. The climatology exhibits strong year-to-year variability but weak decadal variability and a negligible trend. A Canonical Correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
5
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 27 publications
9
94
5
3
Order By: Relevance
“…On average, we find 12 polar-low events per year compared with seven found by Wilhelmsen (1985). Based on the finding of Zahn and von Storch (2008) that there is no significant trend in the polarlow frequency from 1948 up to the present, we believe that this difference is mainly due to differences in methods. The study of Wilhelmsen almost solely relied on meteorological weather maps, which were mainly based on conventional observations.…”
Section: Statistical Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…On average, we find 12 polar-low events per year compared with seven found by Wilhelmsen (1985). Based on the finding of Zahn and von Storch (2008) that there is no significant trend in the polarlow frequency from 1948 up to the present, we believe that this difference is mainly due to differences in methods. The study of Wilhelmsen almost solely relied on meteorological weather maps, which were mainly based on conventional observations.…”
Section: Statistical Resultsmentioning
confidence: 46%
“…The study by Zahn and von Storch (2008) found no significant trend in the polar-low frequency from 1948 to the present. We will assume that this result is valid and also add the data from Wilhelmsen to ours to get a total data set of 21 years.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…COSMO-CLM has been widely used for climatic studies not only over the European continent, Mediterranean Sea and Atlantic Coast (Rockel et al 2008), but also for studying North Atlantic Polar Lows (Zahn and von Storch 2008b), East Asian typhoons (Feser and von Storch 2008) and "Medicanes" in the Mediterranean Sea (Cavicchia and von Storch 2012).…”
Section: Model Usedmentioning
confidence: 99%
“…Polar Lows in the North Atlantic (Zahn and von Storch 2008b) as well as for typhoons in East Asia (Feser and von Storch 2008) are two such sub-synoptic phenomena, thus a methodology has been developed recently to construct a homogeneous data base for the formation and life cycles of such sub-synoptic disturbances. "Homogeneous" refers here to the property that changes in the data base are most likely reflecting changes in the physical reality and not changes in the observational-analytical process.…”
Section: Purpose Of This Studymentioning
confidence: 99%